Maghribi Mabsut Khat in Indonesia: History and Acceptance Factor Analysis - Nurun Najmatul Ulya; Ahmad Yasir Amrulloh; Feri Budiantoro (Fakultas Ushuluddin, Adab dan Humaniora (FUAH) UIN Kiai Haji Achmad Siddiq Jember, 2023)
Islamic calligraphy or khat is the oldest Islamic art found in Indonesia and has experienced a long phase in its development. The peak phase is in Musabaqah Tilawatil Qur'an (MTQ) which includes a khat competition branch Musabaqah Khattil Qur'an (MKQ). MKQ has given many influences to the art of khat, one of which is to ground the seven styles of khat used practically by Indonesian khattat, namely Naskhi, Thuluth, Diwani, Diwani Jali, Farisi, Riq'ah, and Kufi. But, the development of khat in Indonesia does not stop here, 2010 there are Indonesian khattat who managed to achieve international achievements in the branch of the competition for writing khat Maghribi Mabsut, a type of khat from Morocco that has never been recorded in the Indonesian khat universe. The acceptance of this khat continues to expand, as evidenced by the emergence of khatta>t who also managed to make their achievements in the international arena. This study was conducted to answer two questions (1) how is the process of introducing Indonesian khattat to the Maghribi Mabsut khat type? (2) what are the factors that encourage the acceptance of Maghribi Mabsut khat among Indonesian khattat By using field research methods and sociocultural approaches, the results of this study are (1) Maghribi Mabsut khat is known in Indonesia through Indonesian students studying in Egypt (2) there are three factors of acceptance of Maghribi Mabsut khat, namely: education factor, technology adaptation factor and the breadth of opportunity factor.